Hepatic capsular retraction: An updated MR imaging review. Issue 113 (April 2019) - Panick, Catherine E.P.; Ward, Ryan D.; Coppa, Christopher; Liu, Peter S.
Highlights: Hepatic capsular retraction is an uncommon finding that can help to refine a differential diagnosis. The discovery of new entities causing capsular retraction has expanded the differential. MRI allows for improved detection and characterization of lesions causing capsular retraction. Abstract: Hepatic capsular retraction is a morphologic descriptor that refers to invagination or focal flattening of the typical smooth contour of the liver capsule. It is an uncommon finding that, when combined with other imaging features and clinical context, can help to refine the differential diagnosis in patients with liver lesions. Although this descriptor has historically been used in reference to a small subset of benign and malignant lesions, the differential has since been expanded with the discovery of new entities causing capsular retraction as well as with novel and increased use of liver-directed treatment techniques. Additionally, modern imaging techniques now allow for improved detection and characterization of capsular retraction. In this review, we discuss these common and uncommon causes of capsular retraction, with an emphasis on findings from body MRI.